PENYANDERAAN PASIEN TIDAK MAMPU OLEH RUMAH SAKIT TERKAIT PEMBIAYAAN PERAWATAN BERDASARKAN UNDANG-UNDANG RUMAH SAKIT - Brigita E.M Pane; Rebecca Claudia; Joy M.E Manik; Mulyadi (The Juris, 2021)
Hostage taking is an unlawful act that can happen anywhere, such as in a hospital. The hostage-taking occurred due to the patient's inability to pay his hospital expenses. Although the government has provided a lot of help but there is still a lot of discrimination against patients. In this study, the problem is how the position of underprivileged patients in health insurance and legal protection against hostage pasein based on hospital law. The method used in researching the problem is normative method because it needs assessment from various sources and regulations so this method is considered more effective. Based on the research and discussion obtained conclusions that are based on the law on hospitals which in the article states about the social function in the hospital to help poor patients in the form of leniency or the provision of unpaid services to patients who are not able / poor. And also contained in article 6 point (b) law on hospitals which in the article states that all existing governments either in the region or the center have a responsibility to ensure in the health service in the institution for the payment is channeled to the community that has limitations in finance.